Cohesive Devices Used in Argumentative Essays by Undergraduate EFL Learners - Hesti Rokhaniyah; Wildi Adila; Dwi Ana Binti Yulianti (Institut Agama Islam Negeri (IAIN) Kendari, 2022)
Cohesive devices are crucial points recognized as essential features of a good essay, yet employing them in an essay appropriately becomes problematic for learners. This study analyzes qualitatively cohesive devices to investigate EFL learners. It aims at examining how EFL learners apply cohesive devices in argumentative essays, the frequencies of cohesive devices errors in their writings, and the possible causes of EFL learners to produce cohesive devices. Twenty-five learners of the Department of International Relations, at a university in Ponorogo, were requested to produce argumentative essays that consisted of five paragraphs. Twenty-five essays had been identified with the number of errors of grammatical cohesion. Those errors were then analyzed to determine the possible causes affecting the learners’ errors. The find revealed that the number of grammatical cohesion utilized by EFL learners reached 2172, while 168 obtained errors. There was a heavy reliance on cohesive item use. The intralingual transfer mostly influenced the errors produced than the interlingual transfer. The intralingual errors percentage represented 96,9%; interlingual transfer errors reached 3.03%. It occurred due to the learners’ inability to employ the grammar rule. Hence, lecturer should employ the strategies for learners’ writing ability development, such as implementing collaborative learning, delivering the feedback, exposing learners to exercise, and applying a learning management system to result higher level of cohesion.